2022
DOI: 10.1680/jgele.21.00105
|View full text |Cite
|
Sign up to set email alerts
|

Optimised screw pile design for offshore jacket foundations in medium–dense sand

Abstract: Screw piles are well suited foundations for offshore jacket structures, as they can be installed without significant underwater noise and have a large axial capacity. However, installation requirements for such large piles must be reduced to enable their installation in the field. This work combines geometry and installation optimisation to lower force and torque installation requirements. An original pile geometry, composed of a large diameter upper section connected to a smaller diameter lower section by a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The increased stress above the helix can push the pile downward and consequently reduce or even eliminate the vertical installation force. In addition, the increased stress and potential densification in the soil above the helix can result in better monotonic uplift performance [3,4,5,6,7].…”
Section: 𝐴𝑅 = ∆𝑧 𝑝 ℎmentioning
confidence: 99%
“…The increased stress above the helix can push the pile downward and consequently reduce or even eliminate the vertical installation force. In addition, the increased stress and potential densification in the soil above the helix can result in better monotonic uplift performance [3,4,5,6,7].…”
Section: 𝐴𝑅 = ∆𝑧 𝑝 ℎmentioning
confidence: 99%
“…In recent years, research on the installation effect and required load of helical anchors has been increasing, including studies on the disturbed zone, density change, soil parameters after disturbance [8][9][10], lateral earth pressure and uplift or compressive performance after disturbance [11][12][13][14], installation requirements, particle motion during screwing and the torque correlation factor [15][16][17][18]. Some studies have investigated the impact of the installation advancement ratio (AR) on the load-bearing performance of single-helix anchors, where the AR is defined as the ratio of vertical displacement per one rotation ∆z to helix pitch p h [16,19,20]. Cerfontine et al [16,20] found that a lower vertical displacement per rotation can significantly reduce the necessary crowd force during installation or even generate some pull-in, and the uplift stiffness and capacity of the pile were enhanced by this installation process, but the torque remained relatively unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated the impact of the installation advancement ratio (AR) on the load-bearing performance of single-helix anchors, where the AR is defined as the ratio of vertical displacement per one rotation ∆z to helix pitch p h [16,19,20]. Cerfontine et al [16,20] found that a lower vertical displacement per rotation can significantly reduce the necessary crowd force during installation or even generate some pull-in, and the uplift stiffness and capacity of the pile were enhanced by this installation process, but the torque remained relatively unchanged. In addition, the pile capacity in tension generally increases as the AR is reduced and reaches a maximum for AR = 0.5, while the compressive capacity reduces.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, stricter regulations on underwater noise make mitigation methods for pile driving more expensive and silent piling techniques could be used as an alternative [2]. Figure 1(a) describes a new screw pile foundation that meets those two challenges [3].…”
mentioning
confidence: 99%
“…The main challenge during the pile installation is the very low reaction force that may be available offshore at the pile head, which consists only of the pile self-weight and the installation tool. The aim of this work is to demonstrate that screw piles can be installed for offshore applications by rotary jacking at low reaction force, via (geotechnical centrifuge, [2]) and numerical (DEM, [5]) modelling. Figure 1(c) shows the vertical force associated with each pile component during the DEM simulation (AR = 0.5).…”
mentioning
confidence: 99%